1980
DOI: 10.3758/bf03197763
|View full text |Cite
|
Sign up to set email alerts
|

Toxiphobia conditioning with exteroceptive cues

Abstract: The types of conditioned properties acquired by novel (i.e., nonpreexposedl or familiar (i.e., preexposedl exteroceptive cues that were paired with toxicosis, in the absence of a flavor CS, were evaluated in four experiments. In Experiment 1, the conditioned properties of novel exteroceptive cues served to block the acquisition of an aversion to a flavor CS during flavor conditioning and to suppress the ingestion response during flavor testing; animals failed to suppress their ingestion of either the flavor CS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

1982
1982
1998
1998

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 27 publications
0
17
1
Order By: Relevance
“…Instead, it appears to reflect a more general tendency to decrease fluid consumption in the context in which the reinstatement injection was received. Krane (1980) and Willner (1978) have reported a similar decrease in general fluid consumption in a context in which rats received injections of LiCl. Such an effect in the present experiment appears to have occurred independently of any reinstatement of the saccharin aversion, because Group R's preference for saccharin did not decrease as a result of the reinstatement injection.…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations
“…Instead, it appears to reflect a more general tendency to decrease fluid consumption in the context in which the reinstatement injection was received. Krane (1980) and Willner (1978) have reported a similar decrease in general fluid consumption in a context in which rats received injections of LiCl. Such an effect in the present experiment appears to have occurred independently of any reinstatement of the saccharin aversion, because Group R's preference for saccharin did not decrease as a result of the reinstatement injection.…”
Section: Resultsmentioning
confidence: 82%
“…Two considerations suggest the possibility that the present experiments might not have fulfilled this requirement. First, there is evidence to suggest that if exteroceptive (contextual) cues are to be associated with LiCl, they must be novel when they are paired with LiCI (e.g., Archer & Sjoden, 1981;Krane, 1980). In the traditional reinstatement design, the animal is exposed to the US in a familiar context; the test context was not novel when the rats were given reinstatement injections in the present experiments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, subsequent experimental investigations have demonstrated that taste cues are effective in the induction of aversion learning to shock if the CS-US interval can be appropriately adjusted to the temporal characteristics of taste cues (Krane & Wagner, 1975), and that exteroceptive cues can be conditioned to ingestional USs (Delamater, LoLordo, & Berridge, 1986;Krane, 1980) if an appropriate CR measurement is selected or if shock-site is appropriate (Delamater & Tait, 1987). Collectively, these subsequent observations show that task-specific interpretations based on manipulation of general-process factors can provide an alternative interpretation of the retarded-learning observations found with crossover paradigms.…”
Section: Interaction or Crossover Paradigms As A Methodological Basismentioning
confidence: 99%